MINAT MENJADI AKUNTAN PUBLIK DITINJAU DARI MOTIVASI DAN PERSEPSI MENGENAI PASAR KERJA PROFESI AKUNTAN PUBLIK PADA MAHASISWA PROGRAM STUDI AKUNTANSI STIE TRIATMA MULYA - Levina Augustina Dewi; Ni Nyoman Sri Rahayu Trisna Dewi (Universitas Triatma Mulya, 2020)
The objective of this research is to know the influence of Motivation (X1) and Perception of Job Market of Public Accountant Public Profession (X2) to the Interest becoming an Public Accountant (Y) at STIE Triatma Mulya Accounting Department Student either in the simultaneous and partial. The data was obtained by spreading the questionnaires both in the forms of physical and email. Percent of population in this research including an 188 people. The sample collection techniques used in this research is Purposive Sampling. Samples gathered a total of 135 people, but the 100 people back simply from spreading the research has been done. Analysis prerequisite test of this research consisted of Normality Test, Multicolinearity Test, Heteroscedasticity Test. Technique analysis the data used was regression analysis linear multiple. The research results show that Motivation (X1) in the partial had a positive and significant effect to the Interest becoming an Public Accountant (Y), Perception of Job Market of Public Accountant Public Profession (X2) in the partial had a positive and significant effect to the Interest becoming an Public Accountant (Y). In the simultaneous Motivation and Perception of Job Market of Public Accountant Public Profession had a positive effect to the Interest becoming an Public Accountant